Association between sarcopenia and quality of life in quilombola elderly in Brazil - Silva Neto, Luiz Sinésio (Int J Gen Med, 2016)
INTRODUCTION: Currently, there is no single consensual definition of sarcopenia in the literature. This creates a challenge for the evaluation of its prevalence and its direct or indirect impact on the quality of life of elderly populations of different races and ethnicities. Furthermore, no studies as yet have analyzed these variables in populations of elderly subjects of the “quilombola” ethnic group. OBJECTIVE: We aimed to verify the association between sarcopenia and quality of life in quilombola elderly using the Baumgartner and the European Working Group on Sarcopenia in Older People (EWGSOP) criteria. METHODS: This was a cross-sectional study of 70 male and female participants (mean age: 65.58±6.67 years). Quality of life was evaluated using the multidimensional 36-item Short-Form Health Survey (SF-36) of the Medical Outcomes Study. Sarcopenia was diagnosed according to the Baumgartner cutoff for appendicular skeletal muscle mass and the criteria recommended by the EWGSOP. Muscle mass and fat mass percentages were analyzed by dual-energy X-ray absorptiometry, while handgrip strength (HGS) was evaluated using a hand-held dynamometer. Physical performance was assessed through a gait speed test. RESULTS: The prevalence of sarcopenia was 15% according to the Baumgartner cutoff and 10% according to EWGSOP criteria. Quilombola elderly classified as physically active or very active were at least six times less likely to develop sarcopenia than those classified as irregularly active or sedentary. HGS was negatively associated with a diagnosis of sarcopenia according to both sets of criteria. Subjects with sarcopenia reported lower scores than those without the condition on the physical role functioning and bodily pain domains of the SF-36. CONCLUSION: In this sample of quilombola elderly, quality of life was negatively associated with sarcopenia, regardless of the classification criteria used. Additionally, the results showed that diagnostic criteria for sarcopenia should include reductions in lean mass in addition to measures of functioning and physical performance because some subjects showed the former symptom without any alteration of the latter two variables. The cutoff value suggested by Baumgartner criteria were less accurate than that specified by the EWGSOP criteria because they do not consider functioning and physical performance. However, Baumgartner criteria were more sensitive in detecting sarcopenia because reductions in lean mass predict alterations in strength and walking speed.